PAIN AND CREATIVITY ACCORDING TO THE ARTIST “M’HAMED ISSIAKHEM”. AN ANALYSIS OF THE PAINTING “MARTYRS” - Boulakroune Abderrahmane; Ilyas Farah (International Journal of Innovative Technologies in Social Science, 2025)
Our study aims to review the intertwined relationship between pain and creativity of the artist M’hamed Issiakhem through the analysis of his painting "The Martyrs", and sheds light on how the artist embodies pain and psychological conflicts in his artwork by providing a deep vision of the painting “The Martyrs”, and the article addresses the factors that may be influential in enriching artistic creativity through the experience of pain and personal suffering, and highlights the psychological and human dimensions of art and how art can be a means of expressing pain and delivering messages Human suffering. The article reinforces our understanding of the creative spirit and how art can emerge from deep life experiences.